Technical and economic feasibility of hybrid fuel gas & solar power plants in isolated systems - de Araújo, Wellington César [UNESP]; Liberado, Eduardo Verri [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
The use of renewable and alternative energy sources has been encouraged and has grown in recent years, with solar energy composing 2.6% of the Brazilian national energy matrix. However, to democratize and expand its use in remote non-grid-connected regions, it is necessary to search for feasible alternatives to replace diesel-based generators mainly used in isolated systems. Therefore, this paper presents a technical and economic feasibility analysis of a hybrid power generation plant composed of solar and gas sources focused on isolated applications. A case study comparing the proposed hybrid system to a conventional solar off-grid system is also presented.
Keywords: Hybrid plants; Liquefied petroleum gas; Off-Grid; Solar Energy